Determinants of Capital Structure: Empirical Study of Consumer Goods Listing Firm in Indonesia Capital Market - Afriliyati, Nur; Prihatini, Siska; S, Andhika Yudhistira B.; Nainggolan, Paulina; Aprilia, Dian; Gusni (CENTRAL ASIA AND THE CAUCASUS, 2022)
Capital Structure is one of the most researched topics by academics and professionals because it has a direct influence on the enterprise stock value. Many studies have discussed the determinants of capital structure, but the results are still mixed. This paper aims to determine factors affecting the capital structure of consumer goods companies listed in the Indonesia capital market during 2016–2020. This research is a type of applied research with a quantitative approach. This paper use panel data regression with a random effect model to achieve the research goal with sample size is 36 firms selecting by using the purposive sampling technique. The results show that liquidity has a negative effect on the company's capital structure in the consumer goods industry, meanwhile, firm growth and business risk have no effect on the company's capital structure. This condition shows the relevance of the pecking order hypothesis in explaining the determinants of the firm's capital structure in the consumer goods industry